2011
DOI: 10.1007/s11128-011-0314-2
|View full text |Cite
|
Sign up to set email alerts
|

A measure of non-Gaussianity for quantum states

Abstract: We propose a measure of non-Gaussianity for quantum states of a system of n oscillator modes. Our measure is based on the quasi-probability Q(α), α ∈ C n . Since any measure of non-Gaussianity is necessarily an attempt at making a quantitative statement on the departure of the shape of the Q function from Gaussian, any good measure of non-Gaussianity should be invariant under transformations which do not alter the shape of the Q functions, namely displacements, passage through passive linear systems, and unifo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
59
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(64 citation statements)
references
References 44 publications
(54 reference statements)
1
59
2
1
Order By: Relevance
“…In the case of Hilbert-Schmidt degree (2.11) we were able to give an analytic result, while for the fidelity-based degree and the relative-entropy measure we performed numerical evaluations. We found that they depend on the thermal mean occupancȳ n unlike the Wehrl-entropy measure [18]. Our evaluations have also shown a consistent relation between these three non-Gaussianity measures.…”
Section: A Case Study: Damped Photon-added Thermal Statessupporting
confidence: 73%
See 2 more Smart Citations
“…In the case of Hilbert-Schmidt degree (2.11) we were able to give an analytic result, while for the fidelity-based degree and the relative-entropy measure we performed numerical evaluations. We found that they depend on the thermal mean occupancȳ n unlike the Wehrl-entropy measure [18]. Our evaluations have also shown a consistent relation between these three non-Gaussianity measures.…”
Section: A Case Study: Damped Photon-added Thermal Statessupporting
confidence: 73%
“…The non-Gaussianity of the state (4.1) was recently evaluated in Ref. [18] by employing the Wehrl-entropy measure and found to coincide with the non-Gaussianity of the number state |M M|, being thus independent of the thermal mean occupancyn. We employ here Eq.…”
Section: A Case Study: Damped Photon-added Thermal Statesmentioning
confidence: 96%
See 1 more Smart Citation
“…Our method works by reduction to a constrained optimization problem (even for solving the unconstrained SR inequality), so it can be simply adapted to find the MS with an extra constraint on Gaussianity. Several measures of non-Gaussianity have been used in the literature [15,16,[33][34][35]], but we instead suggest using a parameter g capturing the degree of Gaussianity, inspired from our former work on non-Gaussian states with a positive Wigner function [36,37]. Denoting asρ G the Gaussian state that has the same covariance matrix γ (and same mean values x and p ) as stateρ, we define the Gaussianity ofρ as…”
mentioning
confidence: 99%
“…In view of these limitations, it will not come as a surprise that a substantial effort has been put into developing a consistent resource theory of non-Gaussianity. Many non-Gaussianity measures have been proposed and studied in the past decade [31][32][33][34][35][36], that can be applied e.g. to bound the conversion rates between arbitrary states by means of Gaussian operations [35].…”
Section: Introductionmentioning
confidence: 99%